Decision Support System Using Simple Multi-Attribute Rating Technique Method in Determining Eligibility of Assistance - Ikhwan, Ali; Aslami, Nuri (Forum Kerjasama Pendidikan Tinggi, 2022)
Determining the viability of establishing business support for small and medium companies (UKM) is one of the activities that must be assessed carefully and selectively based on the existing evaluation at the Medan City Cooperatives and UKM Office. It is hoped that as a result of this, adequate outcomes for business development help for small and medium companies (UKM) to get assistance funding in business development can be obtained. The solution to the aforementioned issues is to construct a decision support system to aid in determining the feasibility of UKM development assistance. Smart (Simple Multi-Attribute Rating Technique) was chosen to facilitate the aforementioned problem solution by assigning weight to each choice. This decision support system demonstrates how improvements in science and technology may help the Medan City Cooperatives and UKM Office determine the feasibility of village development assistance for the right choice of SMEs based on the proper factors and calculations